Hipsters in their natural habitat - Boddie, Alivia (My University, 2014)
University of Wisconsin--Stout. Research Services
Color poster with text and images.
Keywords: hipsters; loners; bohemians; clubbers; avant-gardes; foodies; Bohemianism--Middle West; Counterculture--Middle West; Posters